Wearable thermoelectric generator with vertically aligned PEDOT:PSS and carbon nanotubes thermoelements for energy harvesting - Hasan, Mohammed Nazibul; Asri, Muhammad Izzudin Ahmad; Saleh, Tanveer; Muthalif, Asan G. A.; Ali, Mohamed Sultan Mohamed (John Wiley and Sons Ltd, 2022)
Thermoelectric generators (TEGs) facilitate maintenance-free sustainable energy transduction, making them attractive and feasible options for selfpowered wearable electronics. Nonetheless, their energy-conversion process suffers from inadequate design and rigidity owing to the use of brittle inorganic materials, making them inapt for wearable applications. Thus, the development of a TEG made of flexible materials with high deformability is required. In this study, a novel wearable TEG was designed and fabricated with vertically aligned p-type PEDOT:PSS and n-type SWCNT film-based thermoelements. Finite element analysis was used to optimize the thermoelement length, which was essential for enhancing the overall TEG output performance. This study also examined the effects of acid-based post-treatment and polyethylenimine concentration on the thermoelectric properties of PEDOT: PSS and SWCNT films, respectively. As a proof of concept, the proposed TEG, composed of five pairs of thermoelements, generated an open-circuit voltage of 1.75 mV while produced a maximum power and a power density of ~6.1 nW and 10.17 nWcm2, respectively, at a ΔT of 11.24C by harvesting energy from the wrist. The proposed design represents a significant step toward developing a next-generation flexible organic TEG that can pave the way for self-powered wearable electronics in a sustainable manner utilizing body heat.